Oversight of next generation nanotechnology - Davies, Clarence J. (Washington, DC, 2009)
"Existing health and safety agencies are unable to cope with the risk assessment, standard setting and oversight challenges of advancing nanotechnology. The nation needs a new agency to address current forms of pollution and to deal with the health and environmental impacts of the technically complex products promised by rapid 21st century scientific advances."